2019
DOI: 10.1111/jcpt.12811
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications with risk of cardiovascular adverse events in the elderly: A systematic review of tools addressing inappropriate prescribing

Abstract: Summary What is known and objective In the last decades, many lists have been developed to screen for inappropriate prescribing. However, information on which potentially inappropriate medications (PIMs) could increase the cardiovascular risk in the elderly is not objectively presented. This review aimed to identify and quantify those PIMs by extracting information from published PIM‐lists. Methods In accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Statement (PRISMA), a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
(74 reference statements)
0
30
0
3
Order By: Relevance
“…Some of these medications can increase the risk of cardiovascular events or even exacerbate underlying conditions. Our previous systematic review showed that there is a restricted number of PIMs described addressing their association with the risk of cardiovascular adverse events 20. Some pharmacotherapeutic groups have been established to be associated with cardiovascular events such as nonsteroidal anti-inflammatory drugs (NSAIDs), antipsychotics, selective calcium channel blockers, and dopaminergic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these medications can increase the risk of cardiovascular events or even exacerbate underlying conditions. Our previous systematic review showed that there is a restricted number of PIMs described addressing their association with the risk of cardiovascular adverse events 20. Some pharmacotherapeutic groups have been established to be associated with cardiovascular events such as nonsteroidal anti-inflammatory drugs (NSAIDs), antipsychotics, selective calcium channel blockers, and dopaminergic agents.…”
Section: Introductionmentioning
confidence: 99%
“…20 Com o objetivo de reduzir o uso de PIM nesta população têm sido desenvolvidos critérios de classificação que permitem avaliar a sua prevalência e desenvolver estratégicas para reduzir a sua utilização. 20,21 Os critérios criados podem ser classificados como explícitos, implícitos ou mistos. 21 Os explícitos constituem listas de medicamentos que podem ser aplicados com a mínima informação e julgamento clínico, não abordando as diferenças individuais entre os doentes, enquanto que os critérios implícitos consideram o regime terapêutico do doente e são baseados no julgamento de um profissional de saúde, sendo específicos para o doente.…”
Section: Introductionunclassified
“…20,21 Os critérios criados podem ser classificados como explícitos, implícitos ou mistos. 21 Os explícitos constituem listas de medicamentos que podem ser aplicados com a mínima informação e julgamento clínico, não abordando as diferenças individuais entre os doentes, enquanto que os critérios implícitos consideram o regime terapêutico do doente e são baseados no julgamento de um profissional de saúde, sendo específicos para o doente. 21 Apesar de não existirem critérios nacionais, Soares et al publicaram em 2008 a operacionalização dos critérios de Beers para Portugal.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Moreover, polypharmacy has been found to be associated with a variety of negative outcomes in older adults, such as falls, mental impairment, cognitive decline, increase of hospital length-of-stay and readmission [11][12][13]. Another important problem is the lack of therapy adherence, given that complex therapeutic regimes are di cult to manage properly [14,15].…”
Section: Introductionmentioning
confidence: 99%